The Color Purple and Namaku Hiroko: Comparative Literature on Gender Inequality Issues - Rizkia Shafarini; Agry Pramita (Jurnal Hawa : Studi Pengarus Utamaan Gender dan Anak, 2022)
This research aims to compare and contrast the gender inequality concerns in Alice Walker's "The Color Purple" and Nh. Dini "Namaku Hiroko." Using a comparative literature method, this research examines the contrasts and similarities in the author's descriptions of gender inequality concerns faced by the major characters in the two novels. The qualitative descriptive analysis approach is used in this investigation. There are parallels in the subject of gender equality for women who are deemed second-class citizens who are sexually and economically objectified and confined by patriarchal society and culture. The distinction between the two novels is that "The Color Purple" exposes the State of American culture that discredits black people, whereas "My Name is Hiroko" depicts women's economic and sexual desires. Finally, we can observe how the authors' cultural backgrounds may impact the literary works they produce since the writers will write about the socio-cultural situations they are experiencing.